Aberrant termination triggers nonsense-mediated mRNA decay. (20th January 2006) - Amrani, N.; Dong, S.; He, F.; Ganesan, R.; Ghosh, S.; Kervestin, S.; Li, C.; Mangus, D.A.; Spatrick, P.; Jacobson, A.
Abstract : NMD (nonsense-mediated mRNA decay) is a cellular quality-control mechanism in which an otherwise stable mRNA is destabilized by the presence of a premature termination codon. We have defined the set of endogenous NMD substrates, demonstrated that they are available for NMD at every round of translation, and showed that premature termination and normal termination are not equivalent biochemical events. Premature termination is aberrant, and its NMD-stimulating defects can be reversed by the presence of tethered poly(A)-binding protein (Pab1p) or tethered eRF3 (eukaryotic release factor 3) (Sup35p). Thus NMD appears to be triggered by a ribosome's failure to terminate adjacent to a properly configured 3′-UTR (untranslated region), an event that may promote binding of the UPF / NMD factors to stimulate mRNA decapping.